Authentication of Indian citrus fruit/fruit juices by untargeted and targeted metabolomics. (February 2017) - Jandrić, Z.; Islam, M.; Singh, D.K.; Cannavan, A.
Abstract: Citrus fruits are one of the most important horticultural crops grown India, and a food commodity that is often targeted for mislabeling worldwide. Authentic citrus fruit samples (Kinnow mandrain ( citrus nobilis x Citrus deliciosa ), Jaffa and Mosambi orange ( Citrus sinensis ), and Red blush grapefruit ( Citrus paradisi )) were obtained from the Indian Agriculture Research Institute and analysed by an untargeted method using ultra performance liquid chromatography-quadrupole-time of flight mass spectrometry to identify characteristic markers that could potentially be used to control citrus fruit authenticity. The most influential markers identified were: didymin, rhoifolin, isorhoifolin, neohesperidin, hesperidin, naringin, narirutin, limonin glucoside, and vicenin-2. A targeted liquid chromatography-tandem mass spectrometry method was then optimised for the analysis of these markers. Ratios of limonin glucoside to hesperidin, narirutin, and didymin; narirutin to hesperidin and vicenin-2; didymin to hesperidin and narirutin; and vicenin-2 to didymin, have the potential to be used to test for authenticity of Indian citrus fruits/fruit juices and to detect adulteration down to 2%. In addition, using an untargeted qualitative approach and applying PCA, it was possible to discriminate between authentic and adulterated samples (down to 1%), by generation of Cooman's plots. Highlights: Authentic citrus fruit samples were analysed by untargeted and targeted methods. Cooman's plots of untargeted data allowed detection of adulteration down to 1%. Ratios of identified markers were used in a targeted method for authenticity. Adulteration with other juices was detected down to 2% using the targeted method.